Desarrollo y medioambiente en Europa: La política energética comunitaria - Sotelo Navalpotro, José A. (Observatorio Medioambiental, 2002)
This article pretends to initiate an approach to energy. There is a pressing need to renew commitment both at Community and Member State level to promote energy efficiency more actively. This is especially true when seen in the light of the Kyoto agreement to reduce CO2 emissions, where improved energy efficiency will play a key role in meeting the EU Kyoto target economically. In addition to a significant positive environmental impact, improved energy efficiency will lead to a more sustainable energy policy and enhanced security of supply, as well as to many other benefits. An estimated economic potential for energy efficiency improvement of more than 18% of present energy consumption still exists today in the EU as a result of market barriers which prevent the satisfactory diffusion of energy-efficient technology and the efficient use of energy. The Action Plan presented below outlines policies and measures for the removal of these barriers and the realisation of this potential.
Keywords: Energy efficiency; Kyoto; positive environmental impact